Active assignment of eigenvalues and eigen-sensitivities for robust stabilization of friction-induced vibration. (June 2017) - Liang, Yao; Yamaura, Hiroshi; Ouyang, Huajiang
Highlights: Eigen-sensitivities of friction-induced asymmetric systems are derived. Robust control input positions against uncertain contact parameters are obtained. Robust stabilization is made by assigning both eigenvalues and eigen-sensitivities. Monte Carlo simulations validate that the robust stabilization method is effective. Critical uncertain contact parameters are confirmed to be μ and c c . Abstract: As friction couples tangential and lateral degrees-of-freedom of a structure at contact interfaces, the resulting asymmetric dynamic system is prone to dynamic instability. Using state-feedback control, such a frictional asymmetric system can be stabilized through assigning the system desirable eigenvalues; but uncertainties in system parameters can cause assigned eigenvalues to deviate from desired locations and thus stability may be lost. This study presents a robust stabilization method that assigns both desirable eigenvalues and their sensitivities and thus render assigned eigenvalues stable and insensitive to perturbations in uncertain contact parameters (the friction coefficient, contact damping, and contact stiffness). This method utilizes receptances of the corresponding symmetric part of the asymmetric system. The optimal control input location is first determined by minimizing the Frobenius norm of the normalized eigen-sensitivity matrix. The normalized eigen-sensitivities indicate that the friction coefficient and contact stiffness intrinsically have similar crucial effects on the stability of the system. To demonstrate the application of the proposed control method, the eigen-sensitivities with respect to only the friction coefficient are assigned. A constrained over-determined least-squares problem is solved to assign both required eigenvalues and eigen-sensitivities. Numerical examples validate the effectiveness of the proposed robust control scheme by Monte Carlo simulations.